A label-free colorimetric aptasensor based on controllable aggregation of AuNPs for the detection of multiplex antibiotics - Wu, Yang-Yang; Huang, Pengcheng; Wu, Fang-Ying (Food chemistry, 2020)
•A colorimetric aptasensor for the detection of multiple antibiotics is presented.•The method allows for multiplex antibiotics detection by the naked eye.•This colorimetric aptasensor displays great tolerance to high salt concentrations.•The method would promote the practical application via RGB analysis of smartphone. We devise a novel colorimetric aptasensor for multiplex antibiotics based on an ss-DNA fragment coordinately controlling gold nanoparticles (AuNPs) aggregation. The multifunctional aptamer (Apt) was elaborately designed to be adsorbed on AuNPs surfaces acting as a binding element for antibiotics and a molecular switch. Chloramphenicol (CAP) and tetracycline (TET) were selected as the model antibiotics. When one kind of antibiotics was added, the specifically recognized fragment of Apt can bind to it and dissociated, and the non-specific one coordinately controls AuNPs aggregation under high-salt conditions. Hence, different color changes of AuNPs solution can be used as the signal readout. The aptasensor exhibited remarkable selectivity and sensitivity for separate detection of TET and CAP, and the detection limits are estimated to be 32.9 and 7.0 nM, respectively. The analysis with the absorption spectroscopy and the smartphone are applied to detect antibiotics in real samples with consistent results and desirable recoveries.